Urea-to-Albumin Ratio and In-Hospital Mortality in Severe Pneumonia Patients - Yu Tian; Yihao Li; Zixin Jiang; Jieru Chen (Canadian Journal of Infectious Diseases and Medical Microbiology)
Objective. The urea-to-albumin ratio (UAR), as a new marker of the systemic inflammatory response, is associated with the mortality in pneumonia patients. However, the association between the UAR and in-hospital mortality in severe pneumonia (SP) has received little attention. Methods. In this single-center retrospective cohort study, 212 SP patients in intensive care unit (ICU) from June 1, 2016, to June 1st, 2020, with baseline UAR were enrolled. The primary outcome was in-hospital mortality. The association of UAR with in-hospital mortality was assessed using a multivariable-adjusted Cox model. Results. Of 212 patients, the median age was 73.0 (61.0, 82.8) years, 70.8% of patients were male, and the APACHE II score was 20.0 (16.0, 26.0). During the hospital period, 101 (47.6%) patients died. In-hospital mortality rates for the lower and higher UAR were 16 (27.6%) and 85 (55.2%), respectively P<0.001. Kaplan–Meier analysis revealed that survival rates were significantly different between the two groups (log rank = 13.71, P<0.001). After adjusted for confounding factors, the higher UAR group was significantly associated with a hazard ratio (HR) for in-hospital mortality of 2.234 (95% confidence interval: 1.146–4.356, P=0.018). Besides, this pattern persisted in subgroup analyses considering sex (HR = 9.380; 95% CI: 2.248–39.138; P=0.002). Conclusions. Higher UAR levels at the commencement of admission to ICU may be independently associated with increased in-hospital mortality in SP patients.